Influence of formulation on physical stability of cherry (Muntingia calabura L.) leaves extract as an antibacterial. Issue 1 (January 2021) - Sultan, A; Parumpu, F A
Abstract: Cherry leaves have been known as an antibacterial and a natural antiseptic that contain flavonoids, saponins and tannins. This research aims to prepare two formulation of cherry leaves extract and to evaluate their physical stability as an antibacterial dosage form. cherry leaves were extracted using ethanol 96% by maceration method. The extract was formulated as a hydrogel with carbomer and a water-based cream with combination of stearic acid and TEA. Physical stability was determined at cool temperature (4°C) and room temperature (± 25°C) by organoleptic, pH, homogeneity, spread, and emulsion type test (for water-based cream). The results showed that all formula of hydrogel was stable in organoleptic, homogeneity and spread test, but the pH value was on 9 which is higher than normal skin pH. Otherwise, the water-based cream was stable in organoleptic, pH and spread test, but in formula 1 showed an emulsion phase separation and formula 3 showed a non-homogeneous arrangement and visible grain after 14 days of storage. Both of the preparation was suitable to applicate cherry leaves extract in antibacterial dosage form with data of skin irritation test.